Desenvolvimento de dispositivo para extração e coleta de fumos de asfalto e aplicação na determinação de hidrocarbonetos policíclicos aromáticos - Ferraz, Luis Manoel do Rosário (2015)
The given work presents the development and usage of a device (DEC Device for Extraction and Collection) capable of generate and collect fumes produced by the heating of asphalt cement samples. The DEC was elaborated aiming its employment on laboratory bench. The heating of the asphalt binder in a closed system generates the fumes. This process occurs under controlled temperature and non-oxidizing atmosphere with hot argon gas as carrier. The fumes are then extracted from small portions of asphalt binder. The developed system was applied on the generation and collection of asphalt binder fumes commercially available in Brazil. The levels of some polycyclic aromatic hydrocarbons (PAH) for the collected fumes were determined. According to the World Health Organization, these compounds must be monitored, regarding their carcinogenic potential. The DEC can operate over a wide temperature range that covers all usual asphalt application temperatures, without any significant losses of the components and without risk of ignition, due to the inert atmosphere. Besides, the present device may operate using different solvents for extraction or even no solvents, through the heating of the sample in question. In addition, the effect of the asphalt cement mass temperature on the PAH levels was discussed in this work. The DEC allows the fume collection either straight from the liquid phase (absorbent solutions) or in solid phase (adsorbent solids). The analysis of the collected fumes using the DEC reported 14 out of the 16 PAH considered high priority by the EPA (Environmental Protection Agency).